585 Chronic Idiopathic Urticaria and Neglected Toxocara Infection - Qualizza, Rosanna (World Allergy Organization Journal, 2012)
BACKGROUND: The diagnosis of chronic idiopathic urticaria is stated when all possible causes of urticaria are excluded. Toxocariasis is a parasitic infection induced by a nematode belonging to the family of Ascaridae with generally affects cats and dogs. Human infestation is caused by the accidental ingestion of embryonated eggs of Toxocara; the larvae do not develop into adult worms but may migrate to several organs, giving rise to a number of clinical expressions, including chronic urticaria. METHODS: From 2005 to 2011 in our Allergy Unit were selected 336 patients with a positive result for IgG antibodies to Toxocara canis as assessed by ELISA or Western blotting (WB). Of them, 52 patients (33 F, 19 M, age ranging from 19 to 76 years old), suffered from chronic urticaria that lasted from 3 to 10 years and was poorly responsive to antihistamines. In all these patients anthelmintic therapy was prescribed using mebendazole (one 100 mg tablet b.i.d. for 3 days), repeated after 20 days up to 3 times. In case of insufficient improvement, albendazole (one 400 mg b.i.d. for 5 days) was used, repeated after 2 months. RESULTS: All patients showed a complete remission of urticaria and a decrease in serum IgG levels to Toxocara canis. In 29 patients (60%) a negative result to ELISA and WB was observed. CONCLUSION: These findings suggest taking into account the role of Toxocara canis in patients with apparent chronic idiopathic urticaria. In patients with positive IgG to Toxocara anthelmintic therapy achieves remission of urticaria.